2013
DOI: 10.1007/s00018-013-1328-y
|View full text |Cite|
|
Sign up to set email alerts
|

The unconventional secretion of stress-inducible protein 1 by a heterogeneous population of extracellular vesicles

Abstract: The co-chaperone stress-inducible protein 1 (STI1) is released by astrocytes, and has important neurotrophic properties upon binding to prion protein (PrP(C)). However, STI1 lacks a signal peptide and pharmacological approaches pointed that it does not follow a classical secretion mechanism. Ultracentrifugation, size exclusion chromatography, electron microscopy, vesicle labeling, and particle tracking analysis were used to identify three major types of extracellular vesicles (EVs) released from astrocytes wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 85 publications
(123 reference statements)
1
51
0
9
Order By: Relevance
“…We previously demonstrated that EVs isolated from astrocyte CM typically express exosomal markers and exhibit classical exosome morphology and size as evidenced by electron microscopy and nanoparticle tracking analysis (NTA). 21 Additionally, our previous data showed that a dominant-negative variant of VPS4A, an AAA-ATPase essential for MVB biogenesis, reduces the release of EVs into astrocyte CM by 85%, indicating that a large fraction of these EVs are composed of exosomes. 21 Our present results pointed out that CM from prnp-null astrocytes derived from ZrchI (prnp (Fig.…”
Section: Prnp Expression Levels Directly Correlate With Exosome Secrementioning
confidence: 97%
See 2 more Smart Citations
“…We previously demonstrated that EVs isolated from astrocyte CM typically express exosomal markers and exhibit classical exosome morphology and size as evidenced by electron microscopy and nanoparticle tracking analysis (NTA). 21 Additionally, our previous data showed that a dominant-negative variant of VPS4A, an AAA-ATPase essential for MVB biogenesis, reduces the release of EVs into astrocyte CM by 85%, indicating that a large fraction of these EVs are composed of exosomes. 21 Our present results pointed out that CM from prnp-null astrocytes derived from ZrchI (prnp (Fig.…”
Section: Prnp Expression Levels Directly Correlate With Exosome Secrementioning
confidence: 97%
“…21 Additionally, our previous data showed that a dominant-negative variant of VPS4A, an AAA-ATPase essential for MVB biogenesis, reduces the release of EVs into astrocyte CM by 85%, indicating that a large fraction of these EVs are composed of exosomes. 21 Our present results pointed out that CM from prnp-null astrocytes derived from ZrchI (prnp (Fig. 1A).…”
Section: Prnp Expression Levels Directly Correlate With Exosome Secrementioning
confidence: 97%
See 1 more Smart Citation
“…[8][9][10] Despite its cytoplasmic localization, HOP is constitutively secreted mainly in extracellular vesicles. 11 Once in the extracellular milieu, HOP (at amino acids (aa) 230-245) interacts with membrane-bound PrP C (at aa 113-128). 12,13 PrP C and HOP have been implicated in cancer progression.…”
Section: Introductionmentioning
confidence: 99%
“…Chaperones have been found in the extracellular environment and play physiological roles such as modulation of the stress response and cell survival (Arruda-Carvalho et al 2007;Lima et al 2007;Beraldo et al 2013;Hajj et al 2013). Hop is secreted by various cells types, including neuronal stem cells (Santos et al 2011), microglia (da Fonseca et al 2012, astrocytes Arantes et al 2009) and cancerous cells such as gliomas (Erlich et al 2007) and ovarian cancer cells (Wang et al 2010;Tsai et al 2012).…”
Section: Extracellular Hop Has Cytokine-like Activitymentioning
confidence: 99%